"We are the best to stand in for patients": a qualitative study on nurses' advocacy characteristics in Ghana - Grace Dadzie; Lydia Aziato; Ama de-Graft Aikins (BMC, 2017)
Abstract Background Patient advocacy has been identified as a core duty of the nurse, and certain nurse characteristics influence the performance of the role. However, these characteristics have not been adequately explored in Ghana. This study aimed to explore the perspectives of nurses about the characteristics of nurses that influence their role as patient advocates. Methods An exploratory descriptive qualitative study was conducted among 15 nurses from a regional hospital in Ghana. Purposive sampling was used to select participants and individual in-depth interviews were conducted in English using a semi-structured interview guide. The interviews were audio-taped and transcribed. Data analysis was done concurrently employing the principles of thematic analysis. Ethical approval was obtained for the study from the Noguchi Memorial Institute of Medical Research and the Ghana Health Service Ethical Review Committee. Results Themes generated revealed nurse traits which enhanced the advocacy role of nurses such as being empathetic, nurturing, ethical, assertive and persistent and nurse states which hindered the performance of the role such as fatigue and frustration. However, "compassionate" emerged as an additional nurse trait from this study. Out of empathy, participants availed themselves for patients to share their problems with them. In their nurturing roles, spending more time with patients and providing personal care fostered closeness which helped in identifying patients' problems. Helping patients navigate the health system was also found. They perceived patient advocacy as a moral responsibility and identified good communication skills and determination to help patients get their problems solved as important in patient advocacy. Some participants also described compassion-based activities such as pleading on patients' behalf, providing material and financial assistance, facilitating care and providing emotional support in their advocacy. However, heavy workload and lack of appreciation from patients were found to hinder the performance of the advocacy role. Conclusions We concluded that nurse characteristics that influence patient advocacy are comparable to those identified internationally such as being empathetic, assertiveness and fatigue. Enhancing these characteristics could help nurses overcome the negative states that undermine the patient advocacy role of nurses.